Carboxylic ester hydrolases: Classification and database derived from their primary, secondary, and tertiary structures - Chen, Yingfei (Protein Sci, 2016)
We classified the carboxylic ester hydrolases (CEHs) into families and clans by use of multiple sequence alignments, secondary structure analysis, and tertiary structure superpositions. Our work for the first time has fully established their systematic structural classification. Family members have similar primary, secondary, and tertiary structures, and their active sites and reaction mechanisms are conserved. Families may be gathered into clans by their having similar secondary and tertiary structures, even though primary structures of members of different families are not similar. CEHs were gathered from public databases by use of Basic Local Alignment Search Tool (BLAST) and divided into 91 families, with 36 families being grouped into five clans. Members of one clan have standard α/β‐hydrolase folds, while those of other two clans have similar folds but with different sequences of their β‐strands. The other two clans have members with six‐bladed β‐propeller and three‐α‐helix bundle tertiary structures. Those families not in clans have a large variety of structures or have no members with known structures. At the time of writing, the 91 families contained 321,830 primary structures and 1378 tertiary structures. From these data, we constructed an accessible database: CASTLE (CArboxylic eSTer hydroLasEs, http://www.castle.cbe.iastate.edu).